A comparative corpus-assisted discourse study of the representations of hosts in promotional tourism discourse. Issue 1 (April 2016) - Jaworska, Sylvia
Abstract : Most research concerned with the representations of hosts in tourism discourse points to the prevalence of stereotypical images of local people asserting that contemporary tourism perpetuates colonial legacy and gendered discursive practices. This claim has been contested, to some extent, in studies that explore representations of hosts in local tourism materials, pointing out that tourism can also resist discursively dominant Western imagery. While this research provides evidence for the existence of hegemonic and diverging discourses about the local 'Other', its empirical basis is rather small and often limited to one context. In this study, I address this shortcoming by examining representations of hosts in a larger corpus of promotional tourism materials, including texts produced by Western and local tourism industries. The data is investigated using the methodology of Corpus-Assisted Discourse Studies (CADS). By comparing external with internal (self-)representations, this study verifies and refines some of the claims on the subject and offers a much more nuanced picture of representations that defies the black-and-white scenarios proposed in previous research.